Themes of resilience in the economics literature: A topic modeling approach - Riepponen, Tapio; Moilanen, Mikko; Simonen, Jaakko (Regional science policy & practice, 2023)
The concept of resilience has been applied in several fields of academic research and has also grown in popularity among economists. The main contribution of this article is the systematic analysis and interpretation of the existing large body of resilience literature in economics by using topic modeling, a modern machine‐learning research method. The advantage of this method is that it offers a more in‐depth understanding of the themes in the resilience literature as opposed to the terminological classifications typically used in bibliometric studies. The results show that the identified topics are spread widely across different subareas of economics and deal with diverse themes, such as adaptation to climate change, stability of the financial system, and various types of shocks in regional economies. The findings reveal that the literature can be divided into two domains: one that deal with incremental changes occurring over a long period of time and the other dealing with unexpected, transient, and sudden changes. Furthermore, according to the results, well‐known, highly cited research papers combine knowledge from different fields. Policymakers seeking to support cutting‐edge research projects may benefit from this finding, as it emphasizes the need for policy measures to enhance cross‐fertilized research. Resumen El concepto de resiliencia se ha aplicado en varios campos de la investigación académica y también ha ganado popularidad entre los economistas. La principal contribución de este artículo es el análisis sistemático y la interpretación de la gran cantidad existente de literatura económica sobre resiliencia que hace uso de modelos temáticos, un moderno método de investigación de aprendizaje automático. La ventaja de este método es que ofrece una comprensión más profunda de los temas de la bibliografía sobre resiliencia, frente a las clasificaciones terminológicas que suelen utilizarse en los estudios bibliométricos. Los resultados muestran que los temas identificados se reparten ampliamente entre distintas subáreas de las ciencias de la economía y tratan temas diversos, como la adaptación al cambio climático, la estabilidad del sistema financiero y diversos tipos de perturbaciones en las economías regionales. Los resultados revelan que la bibliografía puede dividirse en dos ámbitos: uno que trata de los cambios graduales que se producen durante un largo periodo de tiempo y otro que trata de los cambios inesperados, transitorios y repentinos. Además, según los resultados, los trabajos de investigación conocidos y citados frecuentemente combinan conocimientos de campos diferentes. Los responsables políticos que deseen apoyar proyectos de investigación de vanguardia pueden beneficiarse de este hallazgo, ya que pone de relieve la necesidad de medidas políticas para potenciar una investigación que fomente la fecundación cruzada. 抄録 レジリエンスの概念は複数の学術研究分野で採用されており、経済学者の間でも人気が高まっている。本稿の主な趣旨は、現代の機械学習研究方法であるトピックモデリングを使用して、経済学におけるレジリエンスに関する大量の既存の研究論文を体系的に分析し解釈することである。この方法の利点は、書誌学研究で一般的に使用される用語分類とは対照的に、レジリエンスに関する研究論文のテーマをより深く理解できることである。結果から、気候変動への適応、金融システムの安定性、地域経済の様々な種類のショックなど、特定された研究トピックは経済学の様々な下位分野に広く分散しており、多様なテーマが扱われていることが示された。知見から、研究論文は2つの分野に分けられることが明らかになった。1つは長期にわたって起こる漸進的な変化を扱うものであり、もう1つは、予期せぬ、一時的な、突然の変化を扱う分野である。さらには、その結果から、著名で引用数の多い論文は、他の分野の知識を組み合わせている。この知見は、学際的研究を強化するための政策措置の必要性が強調しており、最先端の研究プロジェクトの支援を考える政策立案者はこの知見の恩恵を受ける可能性がある。